Functional xylem characteristics associated with drought‐induced embolism in angiosperms. Issue 6 (19th September 2022) - Lens, Frederic; Gleason, Sean M.; Bortolami, Giovanni; Brodersen, Craig; Delzon, Sylvain; Jansen, Steven
Summary: Hydraulic failure resulting from drought‐induced embolism in the xylem of plants is a key determinant of reduced productivity and mortality. Methods to assess this vulnerability are difficult to achieve at scale, leading to alternative metrics and correlations with more easily measured traits. These efforts have led to the longstanding and pervasive assumed mechanistic link between vessel diameter and vulnerability in angiosperms. However, there are at least two problems with this assumption that requires critical re‐evaluation: (1) our current understanding of drought‐induced embolism does not provide a mechanistic explanation why increased vessel width should lead to greater vulnerability, and (2) the most recent advancements in nanoscale embolism processes suggest that vessel diameter is not a direct driver. Here, we review data from physiological and comparative wood anatomy studies, highlighting the potential anatomical and physicochemical drivers of embolism formation and spread. We then put forward key knowledge gaps, emphasising what is known, unknown and speculation. A meaningful evaluation of the diameter–vulnerability link will require a better mechanistic understanding of the biophysical processes at the nanoscale level that determine embolism formation and spread, which will in turn lead to more accurate predictions of how water transport in plants is affected by drought.